2007
DOI: 10.1080/03054980701425664
|View full text |Cite
|
Sign up to set email alerts
|

Private schools and the millennium development goal of universal primary education: a census and comparative survey in Hyderabad, India

Abstract: Development literature suggests that private schools serving the poor are not part of the solution to meeting the Millennium Development Goal (MDG) of universal primary education. The study conducted a census and survey of schools in notified slums of Hyderabad, India, to contribute to the sparse literature on the nature and extent of private schools for the poor. Of 918 schools found, 60% were found to be private unaided (PUA), enrolling about 65% of total enrolment. On a range of indicators, including pupil-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 4 publications
1
48
0
1
Order By: Relevance
“…At the same time, a growing research agenda has addressed questions about how far increasing choice via an expanded private sector is compatible with the Education For All (EFA) agenda and Millennium Development Goals (MDGs) (Tooley et al, 2007;Härmä, 2009;Woodhead and Streuli 2013;; about the characteristics of private and government schools in terms of quality indicators (The Probe Team, 1999;Pratham, 2012); and whether students studying in the low-fee private sector achieve higher test scores compared to those studying in the government-provided alternative (Chudgar & Quin, 2012;Kingdon, 1996; 1 Operationalized as charging a monthly tuition fee not exceeding about one day's earnings of a daily wage labourer at primary and junior levels (up to Class 8) (Srivastava et al, 2013: 4). Muralhidharan & Kremer, 2006).…”
mentioning
confidence: 99%
“…At the same time, a growing research agenda has addressed questions about how far increasing choice via an expanded private sector is compatible with the Education For All (EFA) agenda and Millennium Development Goals (MDGs) (Tooley et al, 2007;Härmä, 2009;Woodhead and Streuli 2013;; about the characteristics of private and government schools in terms of quality indicators (The Probe Team, 1999;Pratham, 2012); and whether students studying in the low-fee private sector achieve higher test scores compared to those studying in the government-provided alternative (Chudgar & Quin, 2012;Kingdon, 1996; 1 Operationalized as charging a monthly tuition fee not exceeding about one day's earnings of a daily wage labourer at primary and junior levels (up to Class 8) (Srivastava et al, 2013: 4). Muralhidharan & Kremer, 2006).…”
mentioning
confidence: 99%
“…But we could also explain mobility by the perceived quality of education in the low-cost private schools (Oketch et al, 2012;Oketch & Somerset, 2010), that these private schools achieve results with relatively low fees (Tooley & Dixon, 2007). As expressed by teachers, pupil mobility could also be as a result of low-cost private schools having increased in number within the urban informal settlements in SSA countries.…”
Section: Discussionmentioning
confidence: 99%
“…Studies done in the context of the informal settlements in India, Ghana, Nigeria, and Kenya showed that in many instances these low-cost private schools performed better that government schools (Ngware, Abuya, Admassu, Mutisya, & Musyoka, 2013;Tooley & Dixon, 2007). Other scholars have argued that the reason for the rapid growth of the low-cost private schools have been the failure of the government-owned schools to accommodate 629189S GOXXX10.1177/2158244016629189SAGE OpenAbuya and Ngware…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Debates on school choice have gained attention in the South Asian context in recent years, especially in reference to the category of the urban poor (Alderman et al, 2001;Tooley, 2009). Expansion of private school in urban India has occurred in recent times and some scholars have presented evidences that indicate acts of resistance by the poor against the state controlled bureaucratic education system that generally fails to deliver quality education (Tooley et al, 2007;Tooley, 2009). In this context, some studies have highlighted the need to understand the social context of schooling in South Asia and have found flaws with the quality of low-cost private schools (Saragapani, 2009;Sarangapani and Winch, 2010).…”
Section: Introduction:-mentioning
confidence: 99%